Applying Rare Earth Elements, Uranium, and 87Sr/86Sr to Disentangle Structurally Forced Confluence of Regional Groundwater Resources: The Case of the Lower Yarmouk Gorge. (3rd December 2019) - Siebert, Christian; Möller, Peter; Magri, Fabien; Shalev, Eyal; Rosenthal, Eliahu; Al-Raggad, Marwan; Rödiger, Tino
Abstract : The conjoint discussion of tectonic features, correlations of element concentrations, δ 18 O, δ D, and 87 Sr/ 86 Sr of groundwater leads to new insight into sources of groundwater, their flow patterns, and salinization in the Yarmouk Basin. The sources of groundwater are precipitation infiltrating into basaltic rock or limestone aquifers. Leaching of relic brines and dissolution of gypsum and calcite from the limestone host rocks generate enhanced salinity in groundwater in different degrees. High U(VI) suggests leaching of U from phosphorite-rich Upper Cretaceous B2 formation. Both very low U(VI) and specific rare earth element including yttrium (REY) distribution patterns indicate interaction with ferric oxyhydroxides formed during weathering of widespread alkali olivine basalts in the catchment area. REY patterns of groundwater generated in basaltic aquifers are modified by interaction with underlying limestones. Repeated sampling over 18 years revealed that the flow paths towards certain wells of groundwater varied as documented by changes in concentrations of dissolved species and REY patterns and U(VI) contents. In the Yarmouk Gorge, groundwater with basaltic REY patterns but high U(VI) and low Sr 2+ and intermediate sulfate concentrations mainly ascends in artesian wells tapping a buried flower structure fault system crossing the trend of the gorge.